ADAPTASI SETING RUANG SWALAYAN SEBAGAI UPAYA PENCEGAHAN PENYEBARAN COVID-19 DI KOTA PONTIANAK - Ratih, Yudithya; Akbar, Estar Putra; Destria, Caesar (Universitas Aisyiyah Yogyakarta, 2022)
The Corona Virus Deases 19 (Covid-19) pandemic in Pontianak City recorded 2438 Covid-19 confirmations (December 2020). The application of the Covid-19 protocol is one of the efforts to prevent the transmission of the Covid-19 case. Self-service is one of the public facilities continuously visited by the community to meet their daily needs. This study aims to determine which spatial setting variables have changed during the Covid-19 pandemic. Observations were made using the Behavior Mapping method, it was found that the semi-fixed setting variable became the dominant change for preventing the spread of the Covid-19 virus, then a space outside of consciousness (non-fix setting variable) was a place to measure body temperature, while changes fix variable does not occur.